(untitled) (Majalah Kedokteran Bandung, 2023)
One of the causes of cerebral venous sinus thrombosis (CVST) is platelet hyperactivity. Adhesion and secretion are the beginning of platelet activation, which is indicated by a change in the Platelet-selectin (P-selectin) level. The end result of platelet activation is platelet aggregation. However, it is unknown whether the beginning of platelet activation ends with platelet aggregation. This study aimed to discover the correlation between P-selectin level and platelet aggregation in CVST. This study used a cross-sectional escriptive observational correlative approach. Subjects were the CVST outpatients visiting the Neurology Department of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, from July to September 2021. A total of 49 subjects met the inclusion and exclusion criteria. This study used citrate plasma samples for platelet aggregation and serum for P-selectin assessment. Platelet aggregation were assessed using the light transmission platelet aggregation method while P-selectin was assessed using Enzyme-linked immunosorbent assay (ELISA). Platelet aggregation median was 10.6% (range 0.2–82.4%), which reflected normoaggregation. Platelet hyperaggregation were seen in 9 samples (8.4%). Median of P-selectin was 2.4 ng/mL (range 0.1–10.1 ng/mL) which were normal. High P-selectin level was observed in 16 (32.7%) with 4/16 (25%) experiencing platelet hyperaggregation. Statistical analysis showed a weak negative correlation between P-selectin and platelet aggregation (r=-0.012; p=0.467). In conclusion, no correlation is seen between P-selectin and platelet aggregation, which may be due to the fact that platelets are influenced by many factors that are not examined in this study.